Digital technology as mediation in European fine art museums - Reis, Catarina Alexandra Gonçalves dos (2019)
In order to fully understand museums in their current state and the changes that are undergoing, it is crucial to observe their evolution through history. First museums appeared many years ago and nowadays these institutions are present all around the world in different typologies. Museums have been founded to promote civic pride, identity and feelings of belonging, as recreational facilities, educational resources, means to improve quality of life, and to attract tourism. Nowadays, museums are facing some challenges, and the overall trend is to democratize the access. From two decades until now, a change is undergoing, due to social changes that made museums re-evaluate their relationship with the audience. Today, the visitors are seen as individuals, instead of socio-demographic groups. In the last years, museum mediation has been evolving because of the digital technologies. Digital technology was invented in the 20th century, marking what was named as the third technological revolution (Greenwood, 1997). Chappuis et als (2011) report that “Consumer behaviour is shifting rapidly as more people use digital devices and platforms intensively.” (Chappuis, Gaffey and Parvizi, 2011). New technologies started to be seen as solutions to reach visitors in an effective way, independently of their backgrounds. In terms of digital technology as mediation in European fine art museums, the most common are smartphone apps and multimedia guides, but there are also projects using gamming, storytelling, artificial intelligence, augmented/virtual reality and 3D reproductions (Examples of these technologies range from smartphone apps and multimedia guides, to projects using gamming, storytelling, artificial intelligence, augmented/virtual reality and 3D reproductions). To understand the trends, we identified, characterize and studied projects in European Fine Art museums. This information was analysed and allowed to portray the present panorama in European fine art museums towards their visitors through digital means. New policies, strategies and missions are being re-thought. Questions such as how museums must be responsive to the audience needs, open to share knowledge, to create new collaborations and to have an interdisciplinary character, so the cultural experience can be global and diversified are now being discussed. The present work raises questions for the future of museums.